Aerodynamic performance optimization of a vertical-axis wind turbine using blade-spoke connection and pitch angle via the Taguchi method - Tanürün, Himmet Erdi (Bulletin of the Polish Academy of Sciences Technical Sciences, 2026)
In this study, the effect of various parameters on the power coefficient (CP) performance of a vertical axis wind turbine (VAWT) was optimized using the Taguchi method. The optimization was conducted with the Taguchi method, employing three control factors: blade-spoke connection (BSC), turbine blade pitch angle (β), and turbine blade pitch direction (φ). Subsequently, the analysis of variance (ANOVA) method as employed to determine the contribution ratio of each control factor. Regression analysis (RA) was applied to develop an empirical equation predicting the CP of the VAWT, incorporating the control factors. The results indicated an optimal parameter configuration of BSC = 0.5c, β = 2°, and φ = (-), which maximizes the system performance. The performance of the optimal model was observed to exceed that of the conventional VAWT (B1) by 5.82%. Using the ANOVA method, the contribution of parameters on the CP performance of the VAWT was ranked as follows: φ > BSC > β. The φ parameter has the most significant effect at 82.07%, whereas the β parameter exhibits the least effect of 1.17%. Moreover, the predictive accuracy of the developed regression model was validated, yielding R2 values of 0.9221 for the training data and 0.9908 for the test data.